2022
DOI: 10.3390/ijerph192215361
|View full text |Cite
|
Sign up to set email alerts
|

Feedback for Promoting Motor Skill Learning in Physical Education: A Trial Sequential Meta-Analysis

Abstract: Feedback can be used as an effective teaching method in physical education (PE) to promote students’ learning of motor skills. However, there is no objective synthetic evidence to support the role of feedback in PE. Additionally, the effect of each feedback subtype on students’ motor skill learning is still unclear. This study aimed to conduct a meta-analysis and trial sequential analysis (TSA) to evaluate the effects of feedback and feedback subtypes on students’ motor skill learning. Nine databases were sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Based on numerous studies that have demonstrated that KR and KP can improve motor performance in healthy subjects (Doma et al, 2022;Han et al, 2022;Sparrow & Summers, 1992;Zalech & Bujak, 2017) and stroke patients (Chen et al, 2016;Cirstea et al, 2006;Cirstea & Levin, 2007;Kim & Oh, 2019;Molier et al, 2010;Subramanian et al, 2010), we hypothesized that MC could be modified in a similar way.…”
Section: Introductionmentioning
confidence: 99%
“…Based on numerous studies that have demonstrated that KR and KP can improve motor performance in healthy subjects (Doma et al, 2022;Han et al, 2022;Sparrow & Summers, 1992;Zalech & Bujak, 2017) and stroke patients (Chen et al, 2016;Cirstea et al, 2006;Cirstea & Levin, 2007;Kim & Oh, 2019;Molier et al, 2010;Subramanian et al, 2010), we hypothesized that MC could be modified in a similar way.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Legey et al [25], reported that positive MS can help student athletes more active in physical activity. Motor performance skill (MPS) was considered as an important issue and got attention by several major countries in the world [26]. In this study, the global term MPS was used to describe fundamental movement skills including when displaying skills in sports situations [27], such as jumping, running, throwing, hitting [28,29].…”
Section: Introductionmentioning
confidence: 99%